Reduced Fascicle Area Demonstrated in Ilioinguinal Nerves Resected from Primary Inguinal Herniorrhaphy Patients as Evidence of Compression Neuropathy - Robert Wright; Donald E. Born; Troy Sanders; Jordan Landes; Troy Salisbury; Anjali S. Kumar; Makena Horne (Pain Research and Management)
Background and Aim. Previous studies have reported 63% of primary inguinal hernia patients present with apparent enlargement of the ilioinguinal nerve beyond the inguinal ring. This may be due to hernia-related pressure on the canal portion of the ilioinguinal nerve, a form of compression neuropathy. The ilioinguinal nerve of 30 patients was resected near the external inguinal ring during herniorrhaphy and histologically characterized to investigate the underlying cause of the size discrepancy. Methods. 30 male patients with primary inguinal hernias undergoing primary inguinal herniorrhaphy were prospectively recruited for ilioinguinal nerve resection and evaluation. Three samples of the resected ilioinguinal nerve (proximal, canal, and distal) were evaluated using Masson’s trichrome stain to measure fascicle and total nerve cross-sectional area and detect changes in collagen. Results. The fascicle cross-sectional area in the canal segment was significantly decreased compared to the proximal control with a large effect size observed (p=0.016,η2 =0.16). There was no significant difference in the nerve cross-sectional area between locations, but there was a moderate to large effect size observed between locations (p=0.165,η2 =0.105). There was no significant difference in collagen content nor effect size observed between locations (p=0.99,η2 =1.503×10−4). Interpretation. The decrease in the fascicle cross-sectional area within the inguinal canal further suggests that there is chronic pressure applied by hernia tissue consistent with axon degeneration. Collagen content is uniformly distributed along the length of the nerve. Further studies with larger samples are needed to confirm the observed effect of nerve location on the total nerve cross-sectional area and axon loss.